Fabrikasi Paduan Magnesium Berpori dengan Partikel Garam NaCl sebagai Space Holder [Fabrication of Magnesium Alloy Porous by Using NaCl Salt Particle as a Space Holder] - Lestari, Franciska Pramuji (Jurnal Metalurgi, 2018)
Porous magnesium metal is a metal potential as a bone implant because of its light, biodegradable in the body and can accommodate the growth and regeneration of bone tissue cells. The fabrication of magnesium (Mg), calcium (Ca) and zinc (Zn) with porous structures were carried out by powder metallurgy processes using salt particles (NaCl) as a space holders. This study was conducted to produce an isolated and heterogeneous porous metal structure. The various sintering temperatures of 600, 650 and 700 °C with constant holding time at 3 h and the composition of space holder of NaCl (wt.%) 5, 10, and 20 are used for making porous in the Mg-Ca-Zn alloy. Microstructure observation of Mg alloy is carried out by using SEM (scanning electron microscopy), the distribution of elements was done by EDX (energy dispersive x-ray spectroscopy) mapping and also XRD (x-ray diffraction) analysis. Compressive test and % porosity by Archimedes method are carried out to determine the strength of this alloy. NaCl space holder was removed by immersion in ethanol solution and glycerin for 48 h at room temperature. By using 20 wt.% NaCl and sitering temperature of 650 °C revealed high porosity and high compressive strength in Mg alloy. The highest porosity is around 34.57% and the compressive strength is 197.339 MPa. The results showed that the pore structure and mechanical properties were closed to conformity with cortical bone, therefore the porous metal of Mg-Zn-Ca alloy with NaCl as a space holder which was obtained in this study potentially for bone replacement applications.